Compensatory lung growth in autologous lobar implant: Experimental study in dogs - Cataneo, AJM; Cataneo, Daniele Cristina [UNESP] (Elsevier B.V., 2006)
Background. The best way to study compensatory lung growth (CLG) is in a transplant without rejection. Since immunosuppressive drugs may influence CLG, it is better to not use them. Therefore we studied CLG in a reimplant of only one lobe after its removal. The objective was to compare lobar transplant CLG with CLG after lobectomy.Methods. Forty eight dogs were distributed in three groups: G1 = control, G2 = left cranial lobectomy, and G3 = left pneumonectomy with reimplantation of the caudal lobe. Five months after surgery the animals underwent lung scintigraphy and were sacrificed for morphometric study.Results. There was no correlation between scintigraphy and lung mass or lung volume. There was both mass and residual volume CLG in the operated groups, both contralateral and ipsilateral to surgery. There was no compensation for total lung capacity or compliance in the remaining caudal lobe (G2) or the reimplanted caudal lobe (G3) at 5 months after surgery. There was more damage in the reimplanted lobe. As previous studies have shown that CLG starts with increased mass and residual volume and compliance is compensated later. This study seemed to document the beginning of CLG, with lung compliance being the limiting factor of CLG at 5 months.Conclusion. There was CLG in both the reimplanted lobe and the contralateral lung, but compliance was still reduced. CLG was similar in both groups, but in the implanted lobe compliance was more prejudiced.